Living with HIV/AIDS: Stigma and Social Discrimination - Putri, Dewi Kurnia; Malini, Hema; Basmanelly, Basmanelly (Universitas Semarang, 2019)
The diagnose HIV/AIDS in Melayu community is often experience social discrimination and stigma. This situation could lead to mental health disorders among people with HIV/AIDS. This study explores the perceived stigma and social discrimination among people with HIV/AIDS, how they adapt with the situation. Using phenomenological approach, in-depth interview was conducted with seven participants, then analyzed using Collaizi approach. The result showed that most of the participants experienced stigma and lead to received social discrimination from community members such as neighbor, colleagues, relatives, close friend, and even the health professionals. Some of them can adapt well, however, most of them felt anger, depressed, and negative coping such as lying and anti-social. It is recommended to increase social awareness of this situation especially for providing support for people with HIV/AIDS, to improve their quality of life especially their mental health status.